2015
DOI: 10.1111/1365-2435.12403
|View full text |Cite
|
Sign up to set email alerts
|

Differences in thallus chemistry are related to species‐specific effects of biocrust‐forming lichens on soil nutrients and microbial communities

Abstract: Summary 1.It is well-known that vascular plants have species-specific effects on soil properties. However, little is known on how individual species forming biocrusts, communities dominated by lichens, mosses and cyanobacteria that are prevalent in many ecosystems world-wide, affect microbial communities and soil variables related to nutrient cycling. 2. We evaluated the relationship of six biocrust-forming lichens (Buellia epipolia, Diploschistes diacapsis, Fulgensia subbracteata, Psora decipiens, Squamarina … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
75
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(79 citation statements)
references
References 78 publications
(168 reference statements)
4
75
0
Order By: Relevance
“…For example, although we did not measure N in lichen tissue in this study, Delgado-Baquerizo et al (2015) reported that species such as Diploschistes diacapsis (similar to D. thunbergianus here) had the lowest N availability in thalli tissue and soil among the six examined species from the Iberian peninsula, whereas Psora decipiens (similar to P. crystallifera) contained the highest N content. Soil microsites with high N availability for plants have been reported to reduce N 2 O fluxes (Zaman et al, 2009;Liu et al, 2013), likely by promoting AOA and AOB communities, which could explain the lowest N 2 O flux rates under P. crystallifera and X. reptans microsites (Table 1).…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…For example, although we did not measure N in lichen tissue in this study, Delgado-Baquerizo et al (2015) reported that species such as Diploschistes diacapsis (similar to D. thunbergianus here) had the lowest N availability in thalli tissue and soil among the six examined species from the Iberian peninsula, whereas Psora decipiens (similar to P. crystallifera) contained the highest N content. Soil microsites with high N availability for plants have been reported to reduce N 2 O fluxes (Zaman et al, 2009;Liu et al, 2013), likely by promoting AOA and AOB communities, which could explain the lowest N 2 O flux rates under P. crystallifera and X. reptans microsites (Table 1).…”
Section: Discussionmentioning
confidence: 73%
“…lichen species), and their associating microbial communities, modulate the impact of global change drivers on nutrient cycling. A recent study suggested that, similar to vascular plants, biocrust-forming lichens have species-specific effects on soil nutrient cycling and microbial abundance (Delgado-Baquerizo et al, 2015). However, the role of different biocrust-forming species in controlling the response of nutrient cycling (here N transformation processes) to global environmental change remains unresolved.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the significant number of microbial predictors (that is, relative abundance of bacteria and fungi and functional genes), we used a classification Random Forest (RF) analysis (Breiman, 2001) as explained in Delgado-Baquerizo et al (2015) to identify the main microbial predictors of extracellular enzyme activities. The main goal with this analysis is to reduce the number of predictors for further modelling (structural equation modelling).…”
Section: Numerical and Statistical Analysesmentioning
confidence: 99%
“…rproject.org/web/packages/rfPermute/rfPermute.pdf) package for R. After this, and owing to the correlative nature of our data, structural equation modelling (SEM) was used to identify the relative importance and effects of functional genes vs abiotic factors (total C and pH) and microbial composition on soil function (that is, enzyme activities). Unlike regression or analysis of variance, SEM offers the ability to separate multiple pathways of influence and view them as a system (Shipley, 2002;Grace, 2006;Delgado-Baquerizo et al, 2015). Another important capability of SEM is its ability to partition direct and indirect effects that one variable may have on another and estimate the strengths of these multiple effects (Shipley, 2002;Grace, 2006;Delgado-Baquerizo et al, 2015).…”
Section: Numerical and Statistical Analysesmentioning
confidence: 99%
See 1 more Smart Citation